Effects of curing regimes and cement fineness on the compressive strength of ordinary Portland cement mortars - Sajedi, F.; Razak, Hashim Abdul (Elsevier, 2011)
Curing techniques and curing duration have crucial effects on the strength and other mechanical properties of mortars. Proper curing can protect against moisture loss from fresh mixes. The objective of this experimental work is to examine the compressive strength of ordinary Portland cement mortars (OMs) under various curing regimes and cement fineness. Six different curing methods including water, air, water heated, oven heated, air-water, and water-air were applied to the specimens and also six groups of mortars were used. The results showed that the highest and lowest compressive strengths are attributed to the specimens of OPC mortar water cured using grounded OPC for duration of 6 h (OM-G6-wc) and OPC mortar air cured under room temperature with oven heated after demoulding of the specimens at 60 Â°C for duration of 20 h (OM-OH-ac), respectively. The maximum levels obtained of compressive strengths at 7, 28, and 90 days are 57.5, 70.3, and 76.0 MPa, respectively.